ELECTRODE, SECONDARY BATTERY, BATTERY PACK, AND VEHICLE - SASAGAWA TETSUYA; OKI MITSUHIRO; KYUSEKI HIROSHI; MORIMOTO SAYAKA; KOITABASHI YUIKO (2024)
To provide an electrode having excellent cycle performance, a secondary battery including the electrode, a battery pack including the secondary battery, and a vehicle including the battery pack.SOLUTION: According to one embodiment, an electrode is provided. The electrode includes an active material and a titanium-containing solid electrolyte. The active material includes a transition metal oxide. In an X-ray absorption fine structure spectrum, a first X-ray absorption amount I at a first incident X-ray energy for the electrode in a discharged state satisfies 0.2≤I≤0.6. A second X-ray absorption amount at a second incident X-ray energy for anatase titanium dioxide is equal to the first X-ray absorption amount I. The first incident X-ray energy is higher than the second incident X-ray energy.SELECTED DRAWING: Figure 1 【課題】 実施形態は、サイクル性能に優れる電極、該電極を含む二次電池、該二次電池を含む電池パック、並びに、該電池パックを含む車両を提供することを目的とする。【解決手段】 実施形態によれば、電極が提供される。電極は、活物質と、チタン含有固体電解質とを含む。活物質は、遷移金属酸化物を含む。Ｘ線吸収微細構造スペクトルにおいて、放電状態の電極についての第１入射Ｘ線エネルギーにおける第１Ｘ線吸収量Ｉが、０．２≦Ｉ≦０．６を満たす。アナターゼ型二酸化チタンについての第２入射Ｘ線エネルギーにおける第２Ｘ線吸収量が、第１Ｘ線吸収量Ｉと等しい。第１入射Ｘ線エネルギーは、第２入射Ｘ線エネルギーよりも高い。【選択図】 図１